Trask's historical linguistics 2026-02-16T04:37:19+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Millar, Robert McColl (Hodder Arnold, 2007)

(untitled)
Written in an engaging style and illustrated with examples from a wide range of languages, this book is an introduction to historical linguistics - the study of language change over time